Development of a Baby Food Pureed with Probiotic Microorganisms for an Infant from 6 to 12 Months (2020)
ABSTRACT: The infant population and more specifically infants between 6 to 12 months are the most vulnerable to suffering from diseases that jeopardize the immune conditions of their developing organism. To counteract this, this research aimed to: develop a functional food baby pureed for an infant aged 6 to 12 months, using a probiotic strain, where the probiotic strain studied was Bacillus coagulans. The methodology involved the preparation of 3 flavors of baby food pureed such as: ahuyama, carrot and figs, which B. coagulans were added as a functional component. A three-month shelf-life study was determined and evaluated, in which a count was made in the CFU of B. coagulans and its permanence in baby food pureed during this time. It was found that the adequate counting technique is vital for the detection of the microorganism and that carbohydrate content favors its permanence. It was concluded that baby food pureed could have a functional effect seen from the count of B. coagulans and from the study of shelf life as follows: ahuyama up to 90 days, carrot 30 days.